The immunomodulatory phenomenon of vitamin D in the pathogenesis of Multiple Sclerosis - Karolina Raksa; Mateusz Pawlina; Karolina Ziętara; Aleksander Oskroba; Aleksandra Orzechowska; Natalia Pawełczak; Bartłomiej Zielonka; Ilona Kowalczyk; Piotr Pawłowski; Cezary Stawikowski (Kazimierz Wielki University, 2023)
People living in areas with limited access to sunlight, do not produce enough vitamin D and are more likely to suffer from Multiple Sclerosis.Near the equator, where there is high exposure to the sun, the disease is almost non-existent. Aim of the study: The study aimto statistical data on the literature and presents the current state of Vitamin D deficiency as a risk factor in multiple sclerosis. Material and method: The method of study is descriptive epidemiological analysis. Information that has been used is derived from statistical data provided by the WHO. In searching for them on the WHO, PubMed website, Google Scholar, and SCOPUS. Results and conclusions: Vitamin D is a regulator of calcium and phosphorus levels and affects the development and proper functioning of the nervous system. Patients with Multiple sclerosis often have low serum vitamin D levels, which tend to decrease as the disease progresses. There are theories that a deficiency of this vitamin promotes autoimmune, inflammatory demyelination.